HUBUNGAN PELAKSANAAN PRAKTEK DENGAN HASIL PRAKTEK REKAYASA KERJA BATU DAN BETON MAHASISWA JURUSAN TEKNIK SIPIL FT-UNP - 757-768 , Neki Candra (CIVED, 2015)
ABSTRACT The background of this research was the problems faced by building engineering education program students in which they were still lack of discipline, incompetent, and less of cooperative in doing the field practice of stone and concrete engineering-work. In addition, there were many students who got low marks in stone and concrete engineering-work subject. This research aimed at knowing the correlation of the realization of the experiment and the result of the experiment itself. This research was correlational research whose aim was to know whether the correlation of the variable of the research is strong or weak. The population of the research was the whole technique building education program students of Universitas Negeri Padang who took stone and concrete engineering-work subject on January-June 2015. The sample of the research was taken by using cluster random sampling. The sample was all students in a class chosen. The data of the research was collected through observation of the respondents observed when the experiment was in progress.The result of the research showed that there was a correlation of the realization of experiment and the result of the experiment itself. It was emphasized with the result of r that showed the value r = 0,917 with probability Sig. (2tailed) 0,000<0,05. Based on that data, it can be concluded that H0 was rejected and Ha was accepted. Thus, both the realization of experiment and its result have a possitive and significant correlation.   Kata kunci : Pelaksanaan Praktek, Hasil Praktek, Rekayasa Kerja Batu dan   Beton